Machine Learning-based Approach for Prevention of COVID-19 using Steam Vaporizer - Kumar K.S.A.; Sarita K.; Kumar S.; Saket R.K.; Swami A. (My University, 2025)
The present article provides a brief review on Coronavirus Disease-19 (COVID-19) with its prevention using a prototype steam vaporizer developed at home during the lock-down period. The paper discusses the role of Machine Learning (ML) and Artificial Intelligence (AI) for the identification of COVID19. At present, the panic mode and non-availability of anti-drug exponentially increases the COVID-19 cases in India and other parts of the world. This emphasizes humans stay home as a preventing solution to fight against COVID-19. However, staying inside the home is also not safe even when one person is going out for new emergent works. It is also complicated to stay safe from COVID-19 due to a shortage of related preventive measures. Thus, a cheap method of preparing a steam vaporizer is suggested in this paper. Also, its prototype is developed at home with readily available materials. This handheld steam vaporizer has been demonstrated and validated on five people with mild cough and cold symptoms. The survey is carried out using the web page of the COVID 19 survey through the phone. Based on this survey, the person can be informed whether that person is COVID positive or not. The web page for survey is needed to be circulated as much as possible. The tabular and graphically illustrated results show the betterment of this homemade steam vaporizer in mitigating the CoV like viruses. © 2022. GMSARN International Journal. All Rights Reserved.